Types and Abundance of Periphyton in Glass Substrate in Lake Perupuk, Kampung Pinang Village, Perhentian Raja District, Kampar Regency, Riau Province - Santun Tua Siburian; Asmika Harnalin Simarmata; Madju Siagian (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTPeriphyton is a microscopic organism that lives attached to a submerged substrate. This study aims to determine the trophic status based on periphyton on a glass substrate at Lake Perupuk conducted in June-July 2019. There are three sampling stations, namely S1 (at the inlet lake), S2 (in the middle of the lake). lake) and S3 (at the end of the lake). Sampling is done once / week for 3 weeks. Periphyton samples were brushed from glass substrate (8 x 3) cm2. The number of media in S1, S2 and S3 is 24 pieces each. Water quality parameters measured are brightness, temperature, pH, dissolved oxygen, free carbon dioxide, nitrate, and phosphate. The results showed that there were 29 types of periphyton found consisting of 5 classes, namely Bacillariophyceae (11 species), Chlorophyceae (7), Cyanophyceae (6 species), Zygnematophyceae (3 species) and Euglenaphyceae (2 species). The abundance of periphyton in the glass substrate at S1 on the surface was 8,763 cells / cm2, at S2 it was 11,939 cells / cm2 and at S3 on the surface was 21,339 cells / cm2. Water quality parameters are as follows: oxygen range: 5.32-6.40 mg / L, CO2: 5.99-15.98 mg / L, temperature: 28-30 0C, brightness: 44.3-49.3 cm, pH: 5, phosphate: 0.0125-0.0646 mg / L, nitrate: 0.0553-0.2146 mg / L. Data obtained shows that the quality of perupuk lake water is suitable to support periphyton life.    Keywords : Type and abundance, sessile organism, aquatic algae, glass